Pengaruh Knowledge Management, Skills, Ability dan Motivasi Terhadap Kinerja Karyawan Bagian Produksi Pada CV. Nusantara Beton Berkat Bersama Surabaya - Hendro Rumpoko; Indah Kurnia Sari (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The Effect of Knowledge Management, Skills, Ability and Motivation on the Performance of Production Employees at Cv. Nusantara Beton Berkat Bersama Surabaya. Improving employee performance is the most important in every company, where human resources are the main component in carrying out all company production activities. This research was conducted at CV Nusantara Beton Berkat Bersama Surabaya. The purpose of this study was to determine the effect of Knowledge Management, Skills, Ability and Motivation on the Performance of Production Section Employees at CV. Nusantara Beton Berkat Bersama Surabaya both partially and simultaneously. population and samples in this study were all employees of the production section of CV. Nusantara Beton Berkat Bersama Surabaya which amounted to 55 employees. The terms of data analysis in this study are quantitative using the census method using the SPSS V.2 program. The results show that the variables of Knowledge Management, Skills, Ability and Motivation partially and simultaneously affect the performance of employees in the production section of CV. Nusantara Beton Berkat Bersama Surabaya. The coefficient of determination is 0.630 or 63%, this indicates that the variables of Knowledge Management, Skills, Ability and Motivation as a whole have an influence of 63% on employee performance while the remaining 37% is influenced by other variables not examined in this study.